“Modelo de gestión logística de la cooperativa de taxis “ciudad de Quevedo” para el mejoramiento de la calidad - Coello Sión, José Guillermo (2021)
The present research work is based on improving the economic profitability of the units that provide taxi service represented by the Cooperative de taxis "Ciudad de Quevedo", this work consists of carrying out an analysis of the current logistics that the cooperative manages in its functions In order to obtain this information, internal and external tools were implemented such as surveys of the organization's base partners and interviews with the president, with this information objectives are implemented that allow improving the profitability of their service units, considering the proposal that will achieve the improvements. necessary in this organization by implementing the Deming cycle which will allow to implement duly authorized parking spaces, implement a technological application and first quality services, it is essential that all partners and collaborators are aware of all these benefits by implementing a logistics management model that benefits It increases its profitability by reducing resources by providing this service and improving routes, obtaining an efficient and effective service, as well as improving profitability in each of its units. Keywords: Logistics Processes - profitability - Deming Cycle - parking lots